Cybervetting : internet searches for vetting, investigations, and open-source intelligence - Appel, Edward J. (CRC Press, 2015)
Researching an individual's, firm's or brand's online presence has become standard practice for many employers, investigators, and intelligence officers, including law enforcement. Countless companies and organizations are implementing their own policies, procedures, and practices for Internet investigations, cybervetting, and intelligence. Cybervetting: Internet Searches for Vetting, Investigations, and Open-Source Intelligence, Second Edition examines our society's growing dependence on networked systems, exploring how individuals, businesses, and governments have embraced the Internet, in.